(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
This autobiographical piece relates some of the personal experiences of the writer and his reflections on psychotherapy. It begins with his reflections on death and God as a child and, through a brief telling of some of his experiences in therapy and his lived life ends with contemporary reflections on these. It traces lightly through some of his experiences in ’identity politics’ in his personal life and in working in ’mental health’. It ends with some despair about the loss of therapies’ ’radical project’, begun by Freud and the early psychoanalysts and is an invitation to further challenge of the ’being’ of the philosophical tradition and encouragement to explore what writers mentioned call ’becoming’.